Evaluation of the effect of local anesthetic volume and patient age on brachial plexus block with axillary approach - (:unkn) unknown (My University, 2011)
Amaç: Yaşlanma sinirlerde fonksiyonel değişikliğe neden olmaktadır. Yüksek miktardaki lokal anestezik düşük miktardaki lokal anestezikten daha kaliteli blok sağlar. Bu yazıda, genç ve yaşlı yaş gruplarında farklı hacimlerde kullanılan lokal anesteziklerin etkileri geriye dönük olarak, araştırıldı. Gereç ve Yöntem: Yüz dört hastanın duyusal ve motor blok oluşumu ve derlenme süreleri retrospektif olarak değerlendirildi. Hastalar <35 yaş (Grup A) ve >55 yaş (Grup B) olarak iki ana gruba, daha sonra (Grup A) <30 ml veya >30 ml lokal anestezi uygulanan iki alt gruba ayrıldı. Değerlendirmeler bu gruplara dayanarak yapıldı. Bulgular: Duyusal ve motor blok oluşumu zamanı A grubu hastalar ile karşılaştırıldığında B grubu hastalarda <30 ml grupta daha kısa bulundu (p<0,05). B grubu hastalarda blok oluşumu <30 ml lokal anestezik verilen grupta >30 ml verilen gruba göre anlamlı olarak daha hızlı idi (p<0,05). Sonuç: Düşük lokal anestezik hacimleri yaşlı hastalarda gençlere göre duyu ve motor blok oluşma zamanını hızlandırır. Yüksek lokal anestezik hacmi genç hastalarda yaşlı hastalara göre duyu ve motor blok çözülme süresini geciktirmektedir.

Objectives: Ageing induces functional changes in the nerves, and larger volumes of local anesthetic provide better quality sensory block than smaller volumes. Consequently, the effects of local anesthetics were retrospectively researched in young and old age groups, based on the different volumes of local anesthetics used. Methods: Sensory and motor block was performed by nerve stimulator, and block formation and recovery times of 104 patients were assessed retrospectively. Patients were divided into two main groups as <35 y (Group A) and >55 y (Group B), and then into two subgroups as those with <30 ml or >30 ml local anesthetic administered. Evaluations were conducted based on these groups. Results: The length of time for the sensory and motor block formation was shorter in Group B patients compared to Group A patients in the <30 ml group (p<0.05). In Group B patients, the block formation was also significantly faster in those given <30 ml local anesthetic compared to those who were given >30 ml (p<0.05). Conclusion: Lower local anesthetic volumes accelerate sensory and motor block formation time in older patients but not in younger patients. Higher local anesthetic volumes delay sensory and motor block recovery time in younger patients but not in older patients.
Aksiller yaklaşımla yapılan brakial pleksus bloğunda hasta yaşı ve lokal anestetik hacminin etkisinin değerlendirilmesi
Keywords: Genel ve Dahili Tıp